Two new genera of predatory katydids (Orthoptera: Tettigoniidae: Meconematinae) from the Amazon rainforest - Mendes, Diego Matheus De Mello; de Oliveira, Jomara Cavalcante; Chamorro-Rengifo, Juliana; Rafael, José Albertino (Zootaxa, 2018)
Meconematinae comprise small predatory katydids. There are currently seven genera and 58 species recorded for the Neotropical region. Two new genera of Phlugidini are described from the Amazon region, Arboraptor gen. nov., type species Arboraptor viridis sp. nov., and Tyrannoraptor gen. nov., type species Tyrannoraptor arboreus (Nickle, 2003) n. comb. A key to the Neotropical genera of Phlugidini is included and we provide a map showing the known distribution plus comments on their behavior observed during fieldwork.